Half a Century of School Management Research: A Bibliometric Analysis - Anam, Fatkul; Asitah, Nur; Purnomo, Agung; Suryandari, Savitri (AL-ISHLAH: Jurnal Pendidikan, 2024)
School management helps owners of educational institutions easier to manage their education system. Good school management will make it easier to achieve the goals of education itself. This paper aims to examine the status and position of the visual map of research in international school management publications using a bibliometric approach. In this study, researchers used document data collected from 2,241 documents published from 1970 to 2020. The results showed that the University of South Africa and Tshilidzi G. Netshitangani are the most active institutions and individual researchers in school management publications. Articles are the most common type of document in school management publications. There are four groups of collaborative researchers in research on the issue of school management publications. In order to classify the body of knowledge resulting from the publication of half a century, this study establishes a clustering of convergence axes associated with school management publications: Schools, Organization and management, Leadership, and Education, abbreviated as SOLE research themes